The lustre of our country : the American experience of religious freedom - Noonan, John T., Jr. (John Thomas), 1926-2017. (Berkeley : University of California Press, 1998)
The Lustre of Our Country demonstrates how the idea of religious freedom is central to the American experience and to American influence on religion around the world.
Prologue. 1. Boston, 1926-1956 -- pt. 1. History. 2. To Kill a Quaker, to Beat a Baptist -- Religious Liberty before the Revolution. 3. JM's Original Insight. 4. The Foremost of Our Political Institutions. 5. God Is Marching On. 6. The Sorceress and the Source -- pt. 2. Problems. 7. The Pilgrim's Process. 8. Durkheim's Dilemma. 9. Martyrs and Crusaders -- pt. 3. Influences. 10. The Flicker from the Forest. 11. In Behalf of the Supreme Commander. 12. American Advisers, American Missionaries. 13. The Light of Revelation and the Lustre of America -- Epilogue. 14. Ten Commandments.
Includes bibliographical references (pages 359-421) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Freedom of religion -- United States -- History; United States -- Church history; Liberté religieuse -- États-Unis -- Histoire; États-Unis -- Histoire religieuse; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Freedom of religion; United States; Godsdienstvrijheid; Verenigde Staten; Christianity; Religion; Philosophy & Religion; Geschichte; Religionsfreiheit; USA; Church history; History; Geschiedenis (vorm)